Epistemological beliefs and their impact on work, subjectivity and learning - Harteis, Christian; Gruber, Hans; Lehner, Franz (Work, subjectivity and learning)

Oser, F. & Spychiger, M.(2005). Lernen ist schmerzhaft. Zur Theorie des Negativen Wissens und zur Praxis der Fehlerkultur - Harteis, Christian (SCHWEIZERISCHE ZEITSCHRIFT FUR BILDUNGSWISSENSCHAFTEN)

How to close the value gap between market and tax values - Mueller, Jens (EcoMod 2006)

Randomness and Secrecy - A Brief Introduction - Blömer, Johannes (Journal of Universal Computer Science (J.UCS))
We give a brief introduction to probabilistic encryptions. This serves as an example how randomness plays a pivotal role in cryptographic systems that satisfy advanced security concepts.

Fault Based Collision Attacks on AES - Blömer, Johannes; Krummel, Volker (Lecture Notes in Computer Science)

Wagner’s Attack on a Secure CRT-RSA Algorithm Reconsidered - Blömer, Johannes; Otto, Martin (Lecture Notes in Computer Science)

Sign Change Fault Attacks on Elliptic Curve Cryptosystems - Blömer, Johannes; Otto, Martin; Seifert, Jean-Pierre (Lecture Notes in Computer Science)

Influence of adaptive data layouts on performance in dynamically changing storage environments - Brinkmann, Andre; Effert, Sascha; Heidebuer, Michael; Vodisek, Mario (14th Euromicro International Conference on Parallel, Distributed, and Network-Based Processing (PDP'06))
For most of today's IT environments, the tremendous need for storage capacity in combination with a required minimum I/O performance has become highly critical. In dynamically growing environments, a storage management solution's underlying data distribution scheme has great impact to the overall system I/O performance. The evaluation of a number of open system storage visualization solutions and volume managers has shown that all of them lack the ability to automatically adapt to changing access patterns and storage infrastructures; many of them require an error prone manual re-layout of the data blocks, or rely on a very time consuming re-striping of all available data. This paper evaluates the performance of conventional data distribution approaches compared to the adaptive virtualization solution V:DRIVE in dynamically changing storage environments. Changes of the storage infrastructure are normally not considered in benchmark results, but can have a significant impact on storage performance. Using synthetic benchmarks, V:DRIVE is compared in such changing environments with the non-adaptive Linux logical volume manager (LVM). The performance results of our tests clearly outline the necessity of adaptive data distribution schemes.

The influence of habitual protein intake in early childhood on BMI and age at adiposity rebound: results from the DONALD Study - Günther, A L B; Buyken, Anette; Kroke, A (International Journal of Obesity)

REVIS – Reform der Ernährungs- und Verbraucherbildung in Schulen - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Zur Analyse von Unterrichtsmaterialien für die Ernährungs- und Verbraucherbildung - Methfessel, B.; Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Gesundheits- und Innovationsmanagement

Pattern-based Reengineering of Software Systems - Meyer, Matthias (Proceedings of the 13th Working Conference on Reverse Engineering (WCRE 2006), Benevento, Italy)

A Prototype for Guideline Checking and Model Transformation in Matlab/Simulink - Giese, Holger; Meyer, Matthias; Wagner, Robert (Proc. of the 4th International Fujaba Days 2006, Bayreuth, Germany)

On Semantic Issues in Story Diagrams - Tichy, Matthias; Meyer, Matthias; Giese, Holger (Proc. of the 4th International Fujaba Days 2006, Bayreuth, Germany)

Entwicklung von Geschäftsprozessmustern zur Qualitätssicherung - Holtmann, Jörg

Survivable Monitoring in Dynamic Networks - Ateniese, Giuseppe; Riley, Chris; Scheideler, Christian (IEEE Trans. Mob. Comput.)

Distributed coloring in O/spl tilde/(/spl radic/(log n)) bit rounds - Kothapalli, Kishore; Scheideler, Christian; Onus, Melih; Schindelhauer, Christian (IPDPS)

Robust Random Number Generation for Peer-to-Peer Systems - Awerbuch, Baruch; Scheideler, Christian (OPODIS)

Towards a scalable and robust DHT - Awerbuch, Baruch; Scheideler, Christian (SPAA)

Mechanical and Hybrid Joining - Meschut, Gerson (Magnesium Technology)

„Wir wollen die Fügeprozesskosten ganzheitlich reduzieren“ - Meschut, Gerson

Mechanisches Fügen höherfester Stähle im Fahrzeugbau - Meschut, Gerson; Timm, M.; Draht, T.

Self-Coordinating Systems: The Next Challenge in Research on Distributed Systems
We present a parallel algorithm for the rendering of complex three-dimensional scenes. The algorithm runs across heterogeneous architectures of PC-clusters consisting of a visualization-node, equipped with a powerful graphics adapter, and cluster nodes requiring weaker graphics capabilities only. The visualization-node renders a mixture of scene objects and simplified meshes (Reliefboards). The cluster nodes assist the visualization-node by asynchronous computing of Reliefboards, which are used to replace and render distant parts of the scene. Our algorithm is capable of gaining significant speedups if the cluster's nodes provide weak graphics adapters only. We trade the number of cluster nodes off the scene objects' image quality.

Foundations of Formal Sciences IV. The History of the Concept of Formal Sciences

New trends in parallel and distributed computing - Monien, Burkhard; Meyer auf der Heide, Friedhelm

Optical switching in metallic photonic crystal slabs with photoaddressable polymers - Nau, D.; Bertram, R.P.; Buse, K.; Zentgraf, Thomas; Kuhl, J.; Tikhodeev, S.G.; Gippius, N.A.; Giessen, H. (Applied Physics B)

Metallodielectric photonic crystal superlattices: Influence of periodic defects on transmission properties - Zentgraf, Thomas; Christ, A.; Kuhl, J.; Gippius, N. A.; Tikhodeev, S. G.; Nau, D.; Giessen, H. (Physical Review B)

Resonances of split-ring resonator metamaterials in the near infrared - Rockstuhl, C.; Zentgraf, Thomas; Guo, H.; Liu, N.; Etrich, C.; Loa, I.; Syassen, K.; Kuhl, J.; Lederer, F.; Giessen, H. (Applied Physics B)

Disorder issues in metallic photonic crystals - Nau, D.; Schönhardt, A.; Bauer, C.; Christ, A.; Zentgraf, Thomas; Kuhl, J.; Giessen, H. (physica status solidi (b))

Interaction between localized and delocalized surface plasmon polariton modes in a metallic photonic crystal - Christ, A.; Zentgraf, Thomas; Tikhodeev, S. G.; Gippius, N. A.; Martin, O. J. F.; Kuhl, J.; Giessen, H. (physica status solidi (b))

Controlling the interaction between localized and delocalized surface plasmon modes: Experiment and numerical calculations - Christ, A.; Zentgraf, Thomas; Tikhodeev, S. G.; Gippius, N. A.; Kuhl, J.; Giessen, H. (Physical Review B)

Directional Communication in Mobile Ad Hoc Networks - Grünewald, Matthias; Meyer auf der Heide, Friedhelm; Rührup, Stefan; Schindelhauer, Christian; Volbert, Klaus (New Trends in Parallel & Distributed Computing, 6th Int. Heinz Nixdorf Symposium)

Distributional data and grammatical structures: The case of so- called subject extraposition - Mindt, Ilka (Zeitschrift für Anglistik und Amerikanistik 54.2, Special issue on "The scope and Limits of Corpus Linguistics – Empiricism in the Description and Analysis of English)

Computing Clustering Coefficients in Data Streams - Sohler, Christian; Frahling, Gereon; Marchetti-Spaccamela, Alberto; Leonardi, Stefano; Buriol, Luciana (Proceedings of the European Conference on Complex Systems (ECCS'06))
We present random sampling algorithms that with probability at least 1 - δ compute a (1 ± ǫ)- approximation of the clustering coefficient, the transitiv ity coefficient, and of the number of bipartite cliques in a graph given as a stream of edges. Our methods can be extended to approximately count the number of occurences of fixed constant-size subgraphs. Our a lgorithms only require one pass over the input stream and their storage space depends only on structural parameters of the graphs, the approxi- mation guarantee, and the confidence probability. For examp le, the algorithms to compute the clustering and transitivity coefficient depend on that coefficient but n ot on the size of the graph. Since many large social networks have small clustering and transitivity coe fficient, our algorithms use space independent of the size of the input for these graphs. We implemented our algorithms and evaluated their performance on networks from different appli- cation domains. The sizes of the considered input graphs varied from about 8, 000 nodes and 40, 000 edges to about 135 million nodes and more than 1 billion edges. For both algorithms we run experiments with a sample set size varying from 100, 000 to 1, 000, 000 to evaluate running time and approximation guarantee. Our algorithms appear to be time efficient for the se sample sizes.

Counting Triangles in Data Streams - Sohler, Christian; Frahling, Gereon; Marchetti-Spaccamela, Alberto; Leonardi, Stefano; Buriol, Luciana

A Distributed O(1)-Approximation Algorithm for the Uniform Facility Location Problem - Sohler, Christian; Gehweiler, Joachim; Lammersen, Christiane (Proceeedings of 18th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
In this paper, we present a randomized constant factor approximation algorithm for the metric minimum facility location problem with uniform costs and demands in a distributed setting, in which every point can open a facility. In particular, our distributed algorithm uses three communication rounds with message sizes bounded to O(log n) bits where n is the number of points. We also extend our algorithm to constant powers of metric spaces, where we also obtain a randomized constant factor approximation algorithm.

Dimensionen der Politik: Aufklärung, Utopie, Demokratie. Festschrift für Richard Saage zum 65. Geburtstag

Power-Aware Collective Tree Exploration - Dynia, Miroslaw; Korzeniowski, Miroslaw; Schindelhauer, Christian (Architecture of Computing Systems - ARCS)

Average and Smoothed Complexity of Geometric Structures - Damerow, Valentina

A Web Computing Environment for Parallel Algorithms in Java - Bonorden, Olaf; Meyer auf der Heide, Friedhelm; Gehweiler, Joachim (Journal on Scalable Computing: Practice and Experience)
We present a web computing library (PUBWCL) in Java that allows to execute tightly coupled, massively parallel algorithms in the bulk-synchronous (BSP) style on PCs distributed over the internet whose owners are willing to donate their unused computation power. PUBWCL is realized as a peer-to-peer system and features migration and restoration of BSP processes executed on it. The use of Java guarantees a high level of security and makes PUBWCL platform- independent. In order to estimate the loss of efficiency inherent in such a Java-based system, we have compared it to our C-based PUB-Library. As the unused computation power of the participating PCs is unpredictable, we need novel strategies for load balancing that have no access to future changes of the computation power available for the application. We develop, analyze, and compare different load balancing strategies for PUBWCL. In order to handle the influence of the fluctuating available computation power, we classify the external work load. During our evaluation of the load balancing algorithms we simulated the external work load in order to have repeatable testing conditions. With the best performing load balancing strategy we could save 39% of the execution time on average and even up to 50% in particular cases, in our test environment.

Distributed Load Balancing in Heterogeneous Peer-to-Peer Networks for Web Computing Libraries - Gehweiler, Joachim; Schomaker, Gunnar (Proceeedings of 10th IEEE/ACM International Symposium on Distributed Simulation and Real Time Applications (DS-RT))
We present a novel architecture for distributed computing in a peer-to-peer network. In particular, we realize the Paderborn University BSP-based Web Computing Library (PUBWCL), which formerly used a centralized client-server architecture for scheduling and load balancing, as a pure peer-to-peer system. Using distributed heterogeneous hash tables (DHHT), our architecture features scheduling and load balancing of tightly coupled, massively parallel algorithms in the bulk-synchronous (BSP) style with a minimal number of migrations.

Das Gedächtnis der Literatur. Konstitutionsformen des Vergangenen in der Literatur des 20. Jahrhunderts

Shoah in der deutschsprachigen Literatur

Der Kult der Arbeit als Ausgangspunkt für das neue menschliche Gemeinwesen der Zukunft. Émile Zolas „Le Travail“: Ein Urbild des Städtebaus im 20. Jahrhundert - Seng, Eva- Maria (Dimensionen der Politik: Aufklärung, Utopie, Demokratie. Festschrift für Richard Saage zum 65. Geburtstag)

„Im Kopf die Toten verwesen nicht“. Werner Fritschs „Theater des Todes“ - Eke, Norbert Otto (Zeitschrift für deutsche Philologie 125, Sonderheft: Das Gedächtnis der Literatur. Konstitutionsformen des Vergangenen in der Literatur des 20. Jahrhunderts)

Das Gedächtnis der Literatur. Zur Einführung - Eke, Norbert Otto; Allkemper, Alo (Zeitschrift für deutsche Philologie 125, Sonderheft: Das Gedächtnis der Literatur. Konstitutionsformen des Vergangenen in der Literatur des 20. Jahrhunderts)

Thomas Brasch: Fliegen im Gesicht - Eke, Norbert Otto (Deutsche Kurzprosa der Gegenwart)

Herta Müller: Drückender Tango - Eke, Norbert Otto (Deutsche Kurzprosa der Gegenwart)

Konfigurationen der Shoah in der Literatur der DDR - Eke, Norbert Otto (Shoah in der deutschsprachigen Literatur)

Shoah in der deutschsprachigen Literatur - Eke, Norbert Otto (Shoah in der deutschsprachigen Literatur)

Furcht und Schrecken im Theater der Erinnerung oder „Man sollte Komödien schreiben / Leben in diesem trüben Menschenbrei“. Heiner Müllers Tragödie - Eke, Norbert Otto (Die deutsche Tragödie. Neue Lektüren einer Gattung im europäischen Kontext)

A combinatorial algorithm for weighted stable sets in bipartite graphs - Faigle, Ulrich; Frahling, Gereon (Discrete Applied Mathematics)
Computing a maximum weighted stable set in a bipartite graph is considered well-solved and usually approached with preflow-push, Ford–Fulkerson or network simplex algorithms. We present a combinatorial algorithm for the problem that is not based on flows. Numerical tests suggest that this algorithm performs quite well in practice and is competitive with flow based algorithms especially in the case of dense graphs.

A fast k-means implementation using coresets - Frahling, Gereon; Sohler, Christian (Proceedings of the twenty-second annual symposium on Computational geometry - SCG '06)
In this paper we develop an efficient implementation for a k-means clustering algorithm. Our algorithm is a variant of KMHybrid [28, 20], i.e. it uses a combination of Lloyd-steps and random swaps, but as a novel feature it uses coresets to speed up the algorithm. A coreset is a small weighted set of points that approximates the original point set with respect to the considered problem. The main strength of the algorithm is that it can quickly determine clusterings of the same point set for many values of k. This is necessary in many applications, since, typically, one does not know a good value for k in advance. Once we have clusterings for many different values of k we can determine a good choice of k using a quality measure of clusterings that is independent of k, for example the average silhouette coefficient. The average silhouette coefficient can be approximated using coresets.To evaluate the performance of our algorithm we compare it with algorithm KMHybrid [28] on typical 3D data sets for an image compression application and on artificially created instances. Our data sets consist of 300,000 to 4.9 million points. We show that our algorithm significantly outperforms KMHybrid on most of these input instances. Additionally, the quality of the solutions computed by our algorithm deviates less than that of KMHybrid.We also computed clusterings and approximate average silhouette coefficient for k=1,…,100 for our input instances and discuss the performance of our algorithm in detail.

Optimal Temporal Partitioning based on Slowdown and Retiming - Plessl, Christian; Platzner, Marco; Thiele, Lothar (Proc. Int. Conf. on Field Programmable Technology (ICFPT))
This paper presents a novel method for optimal temporal partitioning of sequential circuits for time-multiplexed reconfigurable architectures. The method bases on slowdown and retiming and maximizes the circuit's performance during execution while restricting the size of the partitions to respect the resource constraints of the reconfigurable architecture. We provide a mixed integer linear program (MILP) formulation of the problem, which can be solved exactly. In contrast to related work, our approach optimizes performance directly, takes structural modifications of the circuit into account, and is extensible. We present the application of the new method to temporal partitioning for a coarse-grained reconfigurable architecture.
Keywords: temporal partitioning; retiming; ILP

The Effect of Faults on Network Expansion - Bagchi, Amitabha; Bhargava, Ankur; Chaudhary, Amitabh; Eppstein, David; Scheideler, Christian (Theory Comput. Syst.)

Modeling and Investigation of Robot Swarms - Hamann, Heiko

Jean-Monnet Schriftenreihe: Europäisches Wirtschaftsrecht

Geometric spanners with applications in wireless networks - Schindelhauer, Christian; Volbert, Klaus; Ziegler, Martin (Computational Geometry)

Effectively open real functions - Ziegler, Martin (Journal of Complexity)

Uncomputability Below the Real Halting Problem - Meer, Klaus; Ziegler, Martin (Logical Approaches to Computational Barriers)

MedienPädagogik. Zeitschrift für Theorie und Praxis der Medienbildung

d³FACT insight goes parallel - Aggregation of multiple simulations - Dangelmaier, Wilhelm; Huber, Daniel; Laroque, Christoph; Aufenanger, Mark; Fischer, Matthias; Krokowski, Jens; Kortenjan, Michael (Simulation and Visualization 2006 (SimViS))
In this paper the ideas of a new research project are presented. The material flow simu- lator d3FACT insight shall manage multiple parallel and time synchronous simulations to grand the power of real-time visualization in combination with statistical analysis. This research is issued to overcome the conflict of simulation run repetition for a good statistical basis and real-time immersive visualization. A side effect will be the reduc- tion of time needed for simulation experiments. The planned simulation tool has the feature of triggered cloning, i.e., the user can decide during runtime to clone a set of simulations after changing parameters to preserve the original system. The simulations will be aggregated by visualization and statistics. The rendering is planned to overlay several simulations using effects like inking and transparency. Simulation data will be aggregated with statistical functions and diagrams.

Many-body perturbation theory: The GW approximation - Friedrich, Christoph; Schindlmayr, Arno (Computational Condensed Matter Physics)

Time-dependent density-functional theory - Schindlmayr, Arno (Computational Condensed Matter Physics)

Many-body perturbation theory: The GW approximation - Friedrich, Christoph; Schindlmayr, Arno (Computational Nanoscience: Do It Yourself!)
In this lecture we present many-body perturbation theory as a method to determine quasiparticle excitations in solids, especially electronic band structures, accurately from first principles. The main ingredient is the electronic self-energy that, in principle, contains all many-body exchange and correlation effects beyond the Hartree potential. As its exact mathematical expression is unknown, approximations must be used in practical calculations. The approximation is obtained using a systematic algebraic approach on the basis of Green function techniques. It constitutes an expansion of the self-energy up to linear order in the screened Coulomb potential, which describes the interaction between the quasiparticles and includes dynamic screening through the creation of exchange-correlation holes around the bare particles. The implementation of the approximation relies on a perturbative treatment starting from density functional theory. Besides a detailed mathematical discussion we focus on the underlying physical concepts and show some illustrative applications.

Sublinear-time Algorithms - Sohler, Christian; Czumaj, Artur (EATCS Bulletin)

Towards a paradigm for robust distributed algorithms and data structures - Scheideler, Christian (6th International HNI Symposium on New Trends in Parallel and Distributed Computing)

Dynamische Laufzeitprognose bei Extrudergetrieben. Umsetzung ingenieurwissenschaftlichen Wissens in die industrielle Anwendung - Zimmer, Detmar; Bo, Jianquan (Forschungsforum Paderborn - Paderborner Universitätsmagazin)

Methodik zur funktions-, fertigungs- und prüfgerechten Bemaßung und Tolerierung - Denzer, Vera

Steuerreformen und Übergangsprobleme bei Beteiligungsinvestitionen - Sureth-Sloane, Caren

Entwicklung und Inbetriebnahme einer aktiven Federung für ein geländegängiges Nutzfahrzeug - Schäfer, Erika; Jäker, Karl-Peter; Wielenberg, Andreas (3. VDI/VDE-Fachtagung zur Steuerung und Regelung von Fahrzeugen und Motoren)

A Concept for a Platform-Independent Modelling of Mechatronic Systems: Improving the Re-usability of Models in the Mechatronic Design Process - Gambuzza, Alfonso; Koert, Dirk (Postworkshop Proceedings of the 3rd Workshop on Object-oriented Modeling of Embedded Real-Time Systems (OMER3))

Automatische Codegenerierung für verteilte Informationsverarbeitung in mechatronischen Systemen - Gambuzza, Alfonso; Koert, Dirk; Münch, Eckehard; Voecking, Henner (4. Paderborner Workshop Entwurf mechatronischer Systeme)

Reversible Flügelzellenpumpe für aktive Fahrwerkssysteme - Wielenberg, Andreas; Schäfer, Erika (Konstruktion 3/2006)

An EDF-Based, Hard-Real-Time Communication Engine for Distributed Embedded Systems - De Freitas Francisco, Andre L.; Diez, Marcos (IFIP International Conference on Network and Parallel Computing)

RailCab A New Modular Rail System - Rustemeier, Carsten; Nachtigal, Vitalij (4. Internationale wissenschaftliche Konferenz Trans-Mech-Art-Chem)

Self-Coordinating Systems: The Next Challenge in Research on Distributed Systems - Rammig, Franz-Josef; Dangelmaier, Wilhelm; Karl, Holger; Mertsching, Bärbel; Meyer auf der Heide, Friedhelm; Trächtler, Ansgar (New Trends in Parallel & Distributed Computing)

Aktive Fahrwerkssysteme und ihre Vernetzung - Trächtler, Ansgar (12. Esslinger Forum für Kfz-Mechatronik)

Ein integriertes Hardware-in-the-Loop-System zur Funktionsabsicherung von vernetzten Fahrwerksregelsystemen - Nachtigal, Vitalij; Liu-Henke, Xiaobo (3. VDI/VDE-Fachtagung zur Steuerung und Regelung von Fahrzeugen und Motoren)

Iterative Learning and Self-Optimization Techniques for the Innovative RailCab-System - Trächtler, Ansgar; Münch, Eckehard; Voecking, Henner (Proc. 32nd Annual Conference of the IEEE Industrial Electronics Society – IECON)

Observation of Gradients by Means of Algorithmic Differentiation - Münch, Eckehard; Trächtler, Ansgar (Proc. 32nd Annual Conference of the IEEE Industrial Electronics Society – IECON)

Towards Dynamically Reconfigurable Hard-Real-Time Communication for Embedded Mechatronic Systems - De Freitas Francisco, Andre L. (36th Annual IEEE/IFIP International Conference on Dependable System and Networks)

Computer-Aided Education in Mechatronics with a "Window into the Computer" - Toepper, S.; Lückel, Joachim; Trächtler, Ansgar (4 th IFAC-Symposium on Mechatronic Systems)

Modellbasierte Entwicklung vernetzter, mechatronischer Systeme am Beispiel der Konvoifahrt autonom agierender Schienenfahrzeuge - Giese, Holger; Henkler, Stefan; Hirsch, Martin; Tichy, Matthias; Voecking, Henner (4. Paderborner Workshop Entwurf mechatronischer Systeme)

Potential einer Störgrößenaufschaltung bei der Regelung aktiver Fahrwerke am Beispiel eines geländegängigen Nutzfahrzeugs - Schäfer, Erika; Bruns, Torsten; Wielenberg, Andreas (Paderborner Workshop Entwurf Mechatronischer Systeme (EMS))

Model-based Design of an Active Suspension System Equipped with a Reversible Vane Pump - Wielenberg, Andreas; Schäfer, Erika (5th International Fluid Power Conference)

Railcab - mit innovativer Mechatronik zum Schienenverkehrssystem der Zukunft - Trächtler, Ansgar (VDE Kongress)

Modellierung und Optimierung eines Elastomerlagers für ein aktives Federungssystem für PKW - Poddubny, Wladimir (Forschungsbericht, RtM, Universität Paderborn)

Intersection Management as Self-Organisation of Mechatronic Systems - Bruns, Torsten; Münch, Eckehard (6. Internationales Heinz Nixdorf Symposium)

A Breadth-First Approach for Teaching Computer Graphics - Domik, Gitta; Goetz, Frank (EG Education Papers)

Visual Shaditor: A Seamless Way to Compose High-Level Shader Programs - Goetz, Frank; Domik, Gitta (ACM SIGGRAPH 2006 Research Posters)

Design and Construction of a 3D-Scanning-Laservibrometer - Becker, C; Wedman, S; Hemsel, Tobias (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Piezoelectric transducer design via multiobjective optimization - Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Ultrasonics)
The design of piezoelectric transducers is usually based on single-objective optimization only. In most practical applications of piezoelectric transducers, however, there exist multiple design objectives that often are contradictory to each other by their very nature. It is impossible to find a solution at which each objective function gets its optimal value simultaneously. Our design approach is to first find a set of Pareto-optimal solutions, which can be considered to be best compromises among multiple design objectives. Among these Pareto-optimal solutions, the designer can then select the one solution which he considers to be the best one. In this paper we investigate the optimal design of a Langevin transducer. The design problem is formulated mathematically as a constrained multiobjective optimization problem. The maximum vibration amplitude and the minimum electrical input power are considered as optimization objectives. Design variables involve continuous variables (dimensions of the transducer) and discrete variables (the number of piezoelectric rings and material types). In order to formulate the optimization problem, the behavior of piezoelectric transducers is modeled using the transfer matrix method based on analytical models. Multiobjective evolutionary algorithms are applied in the optimization process and a set of Pareto-optimal designs is calculated. The optimized results are analyzed and the preferred design is determined.
Keywords: Piezoelectric transducer

Multiobjective optimization of piezoelectric transducers using evolutionary algorithms - Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Dynamic Behaviour of Elastic Bodies Coupled by Extended Friction Contacts - Genzo, Alexander; Sextro, Walter (Proceedings of ISMA - International conference on noise and vibration engineering)
Keywords: Noise; Vibration engineering

Unsteady rolling contact of rubber wheels - Gutzeit, F; Sextro, Walter; Kröger, Matthias (Analysis and Simulation of Contact Problems)
This paper presents a model for unsteady longitudinal slippage of a loaded rubber wheel. The aim of modelling was to calculate the dynamical contact behavior in a numerical efficient way. Further on, simulation results are compared to experimental data.

Powder coating fabrication by ultrasonic standing wave atomizer - Hemsel, Tobias; Henning, C; Kauczor, Christopher; Littmann, Walter (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Control of Bundled Miniature Ultrasonic Linear Motors - Hemsel, Tobias; Mracek, Maik (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Piezoelectric linear motor concepts based on coupling of longitudinal vibrations - Hemsel, Tobias; Mracek, Maik; Twiefel, Jens; Vasiljev, Piotr (Ultrasonics)
Classically, rotary motors with gears and spindle mechanisms are used to achieve translatory motion. In means of miniaturization and weight reduction piezoelectric linear motors are of interest. Several ultrasonic linear motors found in literature base on the use of two different vibration modes. Most often flexural and longitudinal modes are combined to achieve an elliptic micro-motion of surface points. This micro-motion is converted to direct linear (or translatory) motion of a driven slider. To gain high amplitudes of the micro-motion and thus having a powerful motor, the ultrasonic vibrator should be driven near the eigenfrequency of its modes. Additionally, low mechanical and electrical losses lead to increased efficiency and large amplitude magnification in resonance. This demands a geometrical design that fits the eigenfrequencies of the two different modes. A frequency-deviation of only a few percent leads to non-acceptable disturbance of the elliptical motion. Thus, the mechanical design of the vibrators has to be done very carefully. Within this contribution we discuss different motor designs based on the coupling of two the same longitudinal vibrations within one structure to generate an elliptic motion of surface points. Different concepts based on piezoelectric plates and Langevin transducers are compared. Benefits and drawbacks against the combination of longitudinal and bending modes will be discussed. Numerical results of the stator vibration as well as motor characteristics are validated by measurements on different prototypes.
Keywords: Piezoelectric linear motor